STRATEGI PEMASARAN DALAM MENINGKATKAN DAYA SAING USAHA MIKRO KECIL MENENGAH (UMKM) (Studi Kasus Pada Usaha Asbac Sport Mataram) - Abdul Basit; Muhamad Sayuti; Vegalyra Novantini Samodra; Sahar; Windiasari, Titin (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2023)
The right marketing strategy or an aggressive strategy. So the right strategy to be used by the Asbac Sport business at this time is a market development strategy, maintaining product quality, maintaining consumer trust, building relationships with other businesses, and developing creativity. This strategy is appropriate because the Asbac Sport business has greater strengths to face its weaknesses and has great opportunities to face its threats. Collaborating with football clubs around NTB so that Asbac Sport products get lots of contacts and lots of orders, Making discounts on products both in terms of price, service and orders, making re-plans or improvements so that the results obtained are more optimal.